Modelo integrado reativo a perturbações em tempo real da programação da produção e controle avançado para um CSTR - Costa, Eugênio Pacceli (2017)
Scheduling and Process Control layers traditionally operate independently in the production process in the process industry. Both the Academy and Industry have been making efforts so that the integration of these layers of decision offers alternatives for improvement in the productive process, while generating better operational results. In particular the determination of optimal product sequencing is sensitive to the transition times obtained from the control layer, which in turn are strongly dependent on the continuous process variables of a chemical plant. In addition, sequencing is also sensitive to (external) demand disturbances occurring in the Scheduling layer, and disturbances (internal) in the process variables, which occur in the control layer. Process perturbations can be characterized by fluctuations in the properties of raw materials or in variations in feed rates. Demand disruptions can be characterized by urgent requests or cancellation of orders. These disturbances may imply rescheduling. The contribution of this work is the development of an integrated model of Scheduling and Multilayer Control adopting the DMC control strategy for a CSTR multiproduct chemical plant. In the review of the literature, no integrated model of Scheduling and Advanced Multi-layered Real-Time Decision-Making for the treatment of demand and process perturbations of a CSTR chemical plant that generated rescheduling was found. Results of the computational simulation of scenarios of the model with several products in a hypothetical chemical plant allow to confirm the viability of its application.